PENGARUH PERILAKU BELAJAR DAN METODE PEMBELAJARAN TERHADAP PEMAHAMAN AKUNTANSI (STUDI KASUS MAHASISWA AKUNTANSI UNIVERSITAS RIAU KEPULAUAN BATAM) - Situmorang, Arman; Santoso, Cahyo Budi (MEASUREMENT : Jurnal Program Studi Akuntansi, 2016)
The purpose of this study were to examine, (1) the significant influence of study behavior to understanding of accounting, (2) the significant influence of learning methods to understanding of accounting, (3) the significant influence of study behavior and learning methods to uderstanding of accounting (case study of accounting student of Universitas Riau Kepulauan Batam)          This research is quantitatif. The population in this research were accounting students of UNRIKA semester 6 and 8. The sample was determined by using the Slovin’s formula with a 5% error tolerance limit as much as 158 samples. The data used in this research are primary data sourced from respondents by distributing questionnaires and secondary data obtained from the Faculty of Econimics BAAK UNRIKA. Data were analyzed  by using multiple linear regression statistical test F and test t.          This research show that (1) Study behavior did not significantly influence to understanding of accounting, (2) learning methods significantly influence to understanding of accounting, (3) simultaneously study behavior and learning methods have a significant influence to understanding  accounting of accounting student of Universitas Riau Kepulauan Batam.Key Words : Study Behavior, Learning Methods, Understanding of Accounting